2013
DOI: 10.1242/jcs.128561
|View full text |Cite
|
Sign up to set email alerts
|

Expression of OA1 limits the fusion of a subset of MVBs with lysosomes; a mechanism likely involved in the initial biogenesis of melanosomes

Abstract: SummaryMultivesicular endosomes/bodies (MVBs) deliver proteins, such as activated EGF receptor (EGFR), to the lysosome for degradation, and, in pigmented cells, MVBs containing PMEL are an initial stage in melanosome biogenesis. The mechanisms regulating numbers and fate of different populations of MVB are unclear. Here, we focus on the role of the G-protein-coupled receptor OA1 (also known as GPR143), which is expressed exclusively in pigmented cells and mutations in which cause the most common type of ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
(64 reference statements)
2
16
0
Order By: Relevance
“…OA1 could inhibit MVB-lysosome fusion through affecting the motility of MVB or lysosome and the luminal pH of MVBs. A delay in lysosomal fusion might allow time for melanin deposition [56]. Taken together, we propose that OA1 may participate in the formation of coat color differences through regulating the number, size, motility and maturation of melanosomes.…”
Section: Discussionmentioning
confidence: 87%
“…OA1 could inhibit MVB-lysosome fusion through affecting the motility of MVB or lysosome and the luminal pH of MVBs. A delay in lysosomal fusion might allow time for melanin deposition [56]. Taken together, we propose that OA1 may participate in the formation of coat color differences through regulating the number, size, motility and maturation of melanosomes.…”
Section: Discussionmentioning
confidence: 87%
“…Within those MVBs, premelanosome protein (PMEL) undergoes proteolytic processing to generate fibrils (fibrillar PMEL) upon which melanin is deposited 13 14 , whereas unprocessed non-fibrillar PMEL and cleaved C-terminal PMEL fragments containing its transmembrane domain traffic along the degradative pathway 15 . We recently showed that the pre-melanosomal G-protein–coupled receptor OA1, when exogenously expressed in HeLa cells, localizes to a subset of MVBs distinct from those carrying ligand-stimulated EGFR 16 . We now find, by immunofluorescence of HeLa cells transfected with markers of melanosome biogenesis, increased co-localization of EGFR with OA1 and fibrillar PMEL in UVC-exposed, compared with EGF-treated, HeLa cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ALIX is recruited to MVBs by binding to the rare lipid lyso-bisphosphatidic acid (LBPA) 30 , which we previously showed to be absent from EGF-stimulated EGFR-containing MVBs 11 , but present in MVBs containing OA1 (ref. 16 ). Here we found extensive co-localization of stress-internalized, but not EGF-stimulated EGFR with LBPA in serum-starved cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the primary observations in the disease OA, caused by mutations in GPR143, is the formation of abnormal 'macromelanosomes' in the RPE and melanocytes [48][49][50]. Macromelanosomes occur through the abnormal growth of melanosomes and may represent a change in organelle motility and geography, in the absence of GPR143 signaling [51], due to the increase of improper transport vesicle fusion with the developing melanosome. Thus, it appears that during melanosome development, GPR143 signaling limits vesicle fusion.…”
Section: Gpr143 Signalingmentioning
confidence: 99%